Sneaksense sensory shoe / Nur Madihah Azuan … [et al.] - Azuan, Nur Madihah; Nazri, Muhammad Asyraf; Johar, Nur Aimi 'Aqilah; Amir, Nuramera; Mohd Norazman, Najwa Nadhirah; Mohammad Faisal Wee, Nur Melissa (Bahagian Penyelidikan dan Jaringan Industri, UiTM Melaka, 2024)
Sensory shoes are a game-changing innovation that aims to improve mobility and safety for people with vision impairments, particularly the blind. These wearable gadgets, built with advanced sensors and haptic feedback systems, deliver real-time environmental feedback through tactile impulses and audible signals. The sensory shoes detect obstacles and changes in the environment within a 2-meter range and provide discrete sound signals to inform users to diverse terrains and hazards, boosting situational awareness and promoting confident navigation. The shoes have an intuitive proximity-based volume control that modifies sound intensity as users approach barriers, resulting in increased awareness and adaptability. Sensory shoes are designed to be comfortable, convenient, and stylish, while also responding to a wide range of needs and preferences. With a concentrate on fostering independence and inclusion, these innovative shoes provide a dependable tool for navigating daily activities securely and effectively. Sensory shoes, which embraces assistive technology principles, seeks to bridge the gap between people with visual impairments and their surroundings, enabling autonomy, confidence, and a higher quality of life. Therefore, sensory shoes not only help users navigate complex situations, but also allow them to participate more completely in social interactions and everyday activities. This innovative footwear technology represents a substantial advancement in assistive solutions, highlighting the potential to transform lives and increase accessibility for all.